If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(80-9x)=x-95
We move all terms to the left:
3(80-9x)-(x-95)=0
We add all the numbers together, and all the variables
3(-9x+80)-(x-95)=0
We multiply parentheses
-27x-(x-95)+240=0
We get rid of parentheses
-27x-x+95+240=0
We add all the numbers together, and all the variables
-28x+335=0
We move all terms containing x to the left, all other terms to the right
-28x=-335
x=-335/-28
x=11+27/28
| 4(2x-6=10x-6 | | 12^-3x=7 | | 14x-5+3x-6=14x+10 | | 12x+24=7x+24 | | x+13=4x+40 | | 15x-5-2(3x)=8.5 | | 15x-6x=3.5 | | .5^(x-3)^1/2=1 | | 5/4+1/3t=3 | | 28x=25x+84 | | x-43=53 | | 8+x/9=2x+1/3 | | 3x-1/5=2x-2/4 | | x+40=185 | | 8x+15=11x-3 | | 0.9=x+0.0875-0.58x | | 8f+6/5=2f | | 7x+5/3=11 | | N+2n=72 | | 8x3 = 6x | | -2(x+10)=3(5-2)+5 | | x^2-195x+9000=0 | | 2(w+6)-4(w-8)=9w+77 | | 8(y+3)=2y | | 11^x=113 | | 24-15=18a+3 | | 11^(x-9)=9^(7x) | | 2(x-5)+14=2(2x+5) | | 4(x-8)-6x=-14 | | 7h+4=2h-6 | | 6z+28=2z+16 | | -10/3=-8r-4/3 |